Floral characteristics and flowering behaviour of Sarawak pepper (Piper nigrum L.) using exagenous hormones. - Johny, Fidelia (2021)
Piper nigrum L. is important cash crops in Sarawak and recently the productivity has been consistently low due to low yield production. Inconsistent of blooming time due to the morphology and heredity of functional male, female, and hermaphrodite flowers in a single spike became one of the factors affected harvesting. As for the exploitation of maximum production, detailed of flower development and composition are important factors to consider. Therefore, the study aims to (i)evaluate the status of pepper farming and flower composition in pepper cultivar varieties in Sarawak, (ii)evaluate the phenology of Sarawak pepper and, (iii)determine the effect of different concentrations of exogenous hormones on berries production. To record farming practices, field surveys were undertaken at 20 pepper farms in Sarawak, and spike samples were selected at random from three pepper vines for each pepper cultivar, namely "Kuching," "Semongok Aman," and "Semongok Emas” then were observed under microsope. Phenology study on “Kuching” cultivar was to identified floral development and two exogenous hormones, then Auxin NAA and Gibberellic acid GA3, were used to increase the hermaphrodite flowers of the "Kuching" cultivar. Four concentrations, i.e., 0 ppm, 10 ppm, 25 ppm, and 50 ppm then applied in a single application during pre-blooming stages. Study found 21% of farmers reported the un-synchronization of berries production in each harvesting time was one of the major constraints in their farming. The composition of flowers found to be varied between cultivar and supported previous pepper farm status where “Kuching” cultivar had less hermaphrodite flower compared to “Semongok Aman” and “Semongok Emas". Nine main stages of inflorescence development (ID) in “Kuching” cultivar and flower sex begin to emerge during the sixth stage with ranged of full berry development takes between 103-150. As for the application of exogenous hormone, GA3 at 25 ppm has the higher percentage of hermaphrodite with 76.62% after 2 weeks of application. The observation continued and showing that vine applied with 25 ppm of NAA up to 83.13% of hermaphrodite. Further, observation continued until week 12 and both GA3 and NAA reported to produce more synchronize berries with 96.01% and 91.87% respectively. Hence, study on the effects of hormones to the growth of hermaphrodite flowers can discover the best types and concentrations hormones to continuously enhance pepper production. Therefore, future studies on economic management including cost assessment of exogenous hormone application, are aspects that need to be considered to describe the economic aspects for small pepper farmers especially in Sarawak to obtain maximum yield through more evenly ripe berry production.